Perlis State branch of the Malaysia Volunteer Corps Department / Mohamad Shafiq Aimar Mohamad Zamir - Mohamad Zamir, Mohamad Shafiq Aimar (Universiti Teknologi MARA, Perlis, 2023)
The focus of this internship report pertains to the extensive six-month industrial training experience I underwent at the Perlis State branch of the Malaysia Volunteer Corps Department, commonly known as Rela. I have been assigned to the Administration Department. As a student specializing in Human Resources, this presents a valuable opportunity for me to apply the knowledge and skills I have acquired during my tenure at Universiti Teknologi MARA (UiTM). The report contains a student profile that includes personal information. A rudimentary resume format was employed to present pertinent details encompassing my personal history, educational background, professional experience, notable achievements, and areas of expertise. The subsequent segment of the report encompasses fundamental details, including the historical background and organizational structure of RELA Perlis. The report also encompassed an account of my training experience, elucidating the specific responsibilities and assignments assigned to me, and elucidating how these experiences contributed to the development and refinement of my skill set. This section also highlights the advantages I gained during my internship period, which significantly impacted my mindset as I prepared to face subsequent challenges. The subsequent section of the report consisted of the SWOT analysis. Strengths, weaknesses, opportunities, and threats have been identified and addressed for Malaysia Volunteers Corps Department (Rela) Perlis State. Suggestions for improving and maintaining the impact in the four components of SWOT analysis have been provided. The internship experience has proven to be highly advantageous and fulfilling for me. This experience has provided me with the ability to adopt multiple perspectives and gain insights into the practical functioning of the professional realm. This particular experience has provided me with a newfound perspective, as my previous exposure to professional settings was limited.